Interactions of HLA-DR and Topoisomerase I Epitope Modulated Genetic Risk for Systemic Sclerosis - Sirilak Kongkaew (2019)
© 2019, The Author(s). The association of systemic sclerosis with anti-Topoisomerase 1 antibody (ATASSc) with specific alleles of human leukocyte antigen (HLA)-DR has been observed among various ethnics. The anti-Topoisomerase 1 antibody is a common autoantibody in SSc with diffuse cutaneous scleroderma, which is one of the clinical subtypes of SSc. On the other hand, an immunodominant peptide of topoisomerase 1 (Top1) self-protein (residues 349–368) was reported to have strong association with ATASSc. In this study, molecular dynamics simulation was performed on the complexes of Top1 peptide with various HLA-DR subtypes divided into ATASSc-associated alleles (HLA-DRB1*08:02, HLA-DRB1*11:01 and HLA-DRB1*11:04), suspected allele (HLA-DRB5*01:02), and non-associated allele (HLA-DRB1*01:01). The unique interaction for each system was compared to the others in terms of dynamical behaviors, binding free energies and solvation effects. Our results showed that three HLA-DR/Top1 complexes of ATASSc association mostly exhibited high protein stability and increased binding efficiency without solvent interruption, in contrast to non-association. The suspected case (HLA-DRB5*01:02) binds Top1 as strongly as the ATASSc association case, which implied a highly possible risk for ATASSc development. This finding might support ATASSc development mechanism leading to a guideline for the treatment and avoidance of pathogens like Top1 self-peptide risk for ATASSc.